The dynamic interacting landscape of MAPL reveals essential functions for SUMOylation in innate immunity - Karine Doiron (Nature Portfolio, 2017)
Abstract Activation of the innate immune response triggered by dsRNA viruses occurs through the assembly of the Mitochondrial Anti-Viral Signaling (MAVS) complex. Upon recognition of viral dsRNA, the cytosolic receptor RIG-I is activated and recruited to MAVS to activate the immune signaling response. We here demonstrate a strict requirement for a mitochondrial anchored protein ligase, MAPL (also called MUL1) in the signaling events that drive the transcriptional activation of antiviral genes downstream of Sendai virus infection, both in vivo and in vitro. A biotin environment scan of MAPL interacting polypeptides identified a series of proteins specific to Sendai virus infection; including RIG-I, IFIT1, IFIT2, HERC5 and others. Upon infection, RIG-I is SUMOylated in a MAPL-dependent manner, a conjugation step that is required for its activation. Consistent with this, MAPL was not required for signaling downstream of a constitutively activated form of RIG-I. These data highlight a critical role for MAPL and mitochondrial SUMOylation in the early steps of antiviral signaling.